EXPLORATIONAL STUDY OF INTERNATIONAL STUDENT MOBILITY PROGRAM CHALLENGES IN DEALING WITH GLOBAL DIVERSITY AND CHANGE - Dian Islami Prasetyaningrum; Hafida Ruminar; Aurora Ivana; Putra Irwandi (Universitas Brawijaya, 2022)
The many opportunities for students to participate in international learning programs, including the International Student Mobility program, must be put to good use. This opportunity is accompanied by challenges that often become obstacles in the learning process. This study aims to explore the challenges faced by students of the International Student Mobility program, which are divided into five factors, namely: academic barriers, social barriers, cultural barriers, and language barriers. Language barrier), and adaptation strategies (adaptation strategies). Using a qualitative approach, interviews were conducted with five research respondents from students of the Faculty of Agriculture, Brawijaya University Malang, who had the opportunity to participate in the International Student Mobility program in various countries in 2021-2022. Fifteen questions were designed to collect data related to the five variables measured, including academic barriers, social barriers, cultural barriers, language barriers, and adaptation strategies. The data collected was then described and analyzed qualitatively.